Mixing non-Newtonian flows in anaerobic digesters by impellers and pumped recirculation. (January 2018) - Meister, Michael; Rezavand, Massoud; Ebner, Christian; Pümpel, Thomas; Rauch, Wolfgang
Highlights: Detailed CFD model for impeller induced mechanical draft tube mixing. Analysis of impeller efficiencies and of the mixing by pumped recirculation. Non-Newtonian flows with different total solids concentrations are investigated. Abstract: In this article, a finite volume method based CFD analysis of the mixing of Newtonian and non-Newtonian flows in anaerobic digesters is conducted. The multiple reference frame method is used to model the mixing which is induced by an impeller rotating within a mechanical draft tube. Moreover, the feeding of biomass is considered in the model formulation. Following the validation of the method against reference data, the mixing of cylindrical and egg-shaped digesters is investigated. The distinguishing feature of this article is that the theoretical findings are adopted for the operation of a real-life anaerobic digester. In the context of a case study slurry flows with high total solids concentrations are investigated.